The Association Between Serum Ferritin Concentration and Visceral Adiposity Estimated by Whole-Body DXA Scan in Women With Polycystic Ovary Syndrome - Adamska, Agnieszka; Łebkowska, Agnieszka; Krentowska, Anna; Adamski, Marcin; Kowalska, Irina (Frontiers in Endocrinology, 2020)
Objective: Women with polycystic ovary syndrome (PCOS) are characterized by insulin resistance and higher prevalence of obesity. Serum ferritin is increased in obesity and is associated with insulin resistance. The aim of the present study was to evaluate the relationships between serum ferritin concentration with insulin resistance and body composition estimated by dual-energy X-ray absorptiometry (DXA) in PCOS women in comparison to the control group. Patients and methods: One hundred and four women were enrolled to the study – 65 women with PCOS and 39 women matched for age and BMI as a control group. Serum ferritin concentration and oral glucose tolerance test (OGTT) were performed. Homeostasis model assessment of insulin resistance (HOMA-IR) was calculated. DXA was performed to estimate fat, fat-free mass and visceral adipose tissue (VAT). Results: Women with PCOS have higher serum concentration of ferritin (p=0.002), insulin at baseline (p=0.03), at 60 min of OGTT (p=0.01), at 120 min of OGTT (p=0.004), HOMA-IR (p=0.03) and VAT (p=0.0001) in comparison to control group. We observed a relationship of serum ferritin with insulin concentration at baseline (r=0.25,p=0.04) and at 120 min of OGTT (r=0.31,p=0.01) and with HOMA-IR (r=0.30,p=0.01) in PCOS group. We noticed an association between serum ferritin concentration and VAT (r=0.42,p=0.001), trunk fat mass (r=0.25,p=0.04) and android fat mass (r=0.25,p=0.04) in PCOS group. Multiple regression analysis revealed that ferritin (p=0.02,β=0.17), insulin at baseline (p=0.001, β=0.30), glucose at the 120 min of OGTT (p=0.007,β=0.26) and triglycerides (p=0.001,β=0.33) were an independent predictors of VAT amount in PCOS women. Conclusions: Elevated serum ferritin concentration is connected with insulin resistance as well as with DXA-estimated VAT, android and trunk fat mass in PCOS women and could be a marker of metabolic dysfunction.